Use of optical coherence tomography, fluorescein angiography and indocyanine green angiography in a screening clinic for wet age-related macular degeneration. Issue 5 (6th December 2006) - Talks, James; Koshy, Zachariah; Chatzinikolas, Konstantinos
Abstract : Aims: To assess the utility of optical coherence tomography (OCT) in a nurse-led, fast-track clinic for new age-related macular degeneration (AMD) referrals, and to see how often indocyanine green angiography (ICGA) led to an additional diagnosis to that provided by fundus fluorescein angiography (FFA). Method: Retrospective audit of a consecutive series of 134 new patients referred with suspected wet AMD. When visual acuity was ⩾6/60 an OCT was performed. If the OCT was consistent with "wet" AMD, the patient underwent simultaneous FFA/ICGA. The sensitivity and specificity of this clinic was calculated. The number of additional diagnoses made using ICGA was recorded. Results: 23/134 (17.16%) patients had OCT only and were not subsequently found to have wet AMD. FFA/ICGA was performed in 111 patients, showing wet AMD in 90 (81%) patients. OCT as used in our clinic had a sensitivity of 1 and a specificity of 0.65 for detecting wet AMD. ICGA provided additional diagnoses in 19 (14.17%) patients. ICGA detected a specific vascular abnormality in 58% of the occult lesions. Conclusions: OCT proved to be an effective screening tool for wet AMD in this clinic, with excellent sensitivity and reasonable specificity. ICGA provided an additional diagnosis in a significant number of cases, but did not define a vascular abnormality in all occult cases.